Blimp-1 prolongs allograft survival without regimen via influencing T cell development in favor of regulatory T cells while suppressing Th1. (July 2018) - Wang, Aline Yen Ling; Loh, Charles Yuen Yung; Chen, Shyi-Jou; Kao, Huang-Kai; Lin, Cheng-Hung; Chuang, Sheng-Hao; Lee, Chin-Ming; Sytwu, Huey-Kang; Wei, Fu-Chan
Highlights: Blimp-1 is expressed in multiple cell lineages and in particular, T cells. It is the first study for allograft survival in Blimp-1 T-cell transgenic mice. Blimp-1 T-cells modulate skin allograft survival without immunosuppression. T-bet reduction and FoxP3 increment occur in Blimp-1 T-cells. Blimp-1 creates a favorable condition via Th1 suppression and Treg amplification. Abstract: Background: B lymphocyte-induced maturation protein 1 (Blimp-1) transcription factor is expressed in multiple cell lineages and in particular, T cells. However, the role of Blimp-1 in T cell-mediated allograft tolerance is still unknown. Methods: This study is the first to investigate transplanted skin allograft survival using transgenic (Tg) mice with T cell overexpression of Blimp-1. Results: Without any immunosuppression, fully MHC-mismatched skin allografts on Tg(+) mice had a significantly prolonged survival rate and partial tolerance at 90 days. Allograft lymphocytic infiltration was decreased in Tg(+) mice and a dampened donor-stimulated alloimmune response was seen. An absolute cell number ratio of inflammatory Th1 and Th17 cells against anti-inflammatory regulatory T (Treg) and IL-10-producing T cells, as well as cytolytic proteins, were significantly decreased in lymphoid organs and allograft. Blimp-1 transgenic T cells displayed an increased Treg differentiation capability and enhanced suppression of T cell proliferation. Overexpression of Blimp-1 in T cells promoted the formation of an anti-inflammatory cell-cytokine composition, both systemically and locally via transcription factor modulation such as T-bet downregulation and FoxP3 upregulation. Discussion: As such, allograft survival was made possible due to Th1 suppression and Treg amplification with the creation of an 'allograft protective microenvironment'.